Correction: Chitosan-gated organic transistors printed on ethyl cellulose as a versatile platform for edible electronics and bioelectronics - Sharova, Alina; Modena, Francesco; Luzio, Alessandro; Melloni, Filippo; Cataldi, Pietro; Viola, Fabrizio; Lamanna, Leonardo; Zorn, Nicolas; Sassi, Mauro; Ronchi, Carlotta; Zaumseil, Jana; Beverina, Luca; et al. (Nanoscale, 2024)
Correction for ‘Chitosan-gated organic transistors printed on ethyl cellulose as a versatile platform for edible electronics and bioelectronics’ by Alina S. Sharova et al., Nanoscale, 2023, 15, 10808-10819, https://doi.org/10.1039/D3NR01051A.